Spatially resolved mass spectrometry analysis of amyloid plaque‐associated lipids. Issue 2 (1st November 2020) - Blank, Martina; Hopf, Carsten
Abstract: Over the last 10 years, considerable technical advances in mass spectrometry (MS)‐based bioanalysis have enabled the investigation of lipid signatures in neuropathological structures. In Alzheimer´s Disease (AD) research, it is now well accepted that lipid dysregulation plays a key role in AD pathogenesis and progression. This review summarizes current MS‐based strategies, notably MALDI and ToF‐SIMS imaging as well as laser capture microdissection combined with LC‐ESI‐MS. It also presents recent advances to assess lipid alterations associated with Amyloid‐β plaques, one of the hallmarks of AD. Collectively, these methodologies offer new opportunities for the study of lipids, thus pushing forward our understanding of their role in such a complex and still untreatable disease as AD. Abstract : Lipids are dynamic multi‐functional molecules and considerable evidence now supports that perturbations in their metabolism can be associated with Aβ deposition and Alzheimer's Disease progression. Our review describes and highlights how spatially resolved mass spectrometry platforms applied to the study of amyloid plaque‐associated lipids can be powerful and reliable research tools providing knowledge basis for future therapeutic strategies as well as important insights into the factors that contribute to Alzheimer's Disease.